2012
DOI: 10.1248/bpb.35.301
|View full text |Cite
|
Sign up to set email alerts
|

Different Involvement of DNA Methylation and Histone Deacetylation in the Expression of Solute-Carrier Transporters in 4 Colon Cancer Cell Lines

Abstract: The purpose of this study on the involvement of epigenetic control of the expression of solute carrier (SLC) transporters by DNA methylation and histone deacetylation in 4 colon cancer cells is to find the epigenetic control mechanisms of drug transporters in colon cancers. Human colon cancer cell lines (HCT116, HT29, SW48, SW480) were treated with 5-aza-2′-deoxycytidine (DAC), as a DNA methyltransferase inhibitor, followed by trichostatin A (TSA), as a histone deacetylase inhibitor. The mRNA expression and DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…17) In our previous study, it was found that 4 CRC cell lines (SW48 and HCT116 cells as MSI; HT29 and SW480 cells as microsatellite stable, MSS) 18) underwent different epigenetic changes of several solute carrier transporters, which have been reported to be involved in the transport of anticancer drugs such as 5-FU. 19) In this study, we examined the potential of epigenetic modifiers as chemo-sensitizers in combination with chemotherapeutic drugs in the 4 CRC cell lines used in our previous study. 19) Different epigenetic modifiers were used, including DAC, AC and zebularine (Zeb) as DNMT inhibitors and TSA, SAHA and valproic acid (VPA) as HDAC inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17) In our previous study, it was found that 4 CRC cell lines (SW48 and HCT116 cells as MSI; HT29 and SW480 cells as microsatellite stable, MSS) 18) underwent different epigenetic changes of several solute carrier transporters, which have been reported to be involved in the transport of anticancer drugs such as 5-FU. 19) In this study, we examined the potential of epigenetic modifiers as chemo-sensitizers in combination with chemotherapeutic drugs in the 4 CRC cell lines used in our previous study. 19) Different epigenetic modifiers were used, including DAC, AC and zebularine (Zeb) as DNMT inhibitors and TSA, SAHA and valproic acid (VPA) as HDAC inhibitors.…”
mentioning
confidence: 99%
“…19) In this study, we examined the potential of epigenetic modifiers as chemo-sensitizers in combination with chemotherapeutic drugs in the 4 CRC cell lines used in our previous study. 19) Different epigenetic modifiers were used, including DAC, AC and zebularine (Zeb) as DNMT inhibitors and TSA, SAHA and valproic acid (VPA) as HDAC inhibitors. The results obtained from this study about the effects of epigenetic modification on the cytotoxicity induced by anticancer drugs will provide information to help understand how to incorporate epigenetic modifiers into the current anticancer armamentarium.…”
mentioning
confidence: 99%
“…SLC19A3 encodes the thiamine transporter expressed at the apical surface of polarized cells (35). SLC19A3 mRNA expression has been shown to be downregulated by DNA methylation in colon cancer cell lines (36). DLEC1 has been demonstrated to act as a tumor suppressor gene in the tumorigenesis and progression of numerous types of carcinoma, such as multiple lymphomagenesis, and thus it may serve as a non-invasive tumor marker (37).…”
Section: Discussionmentioning
confidence: 99%
“…22) Briefly, total RNA was extracted from HCT116 cells by the spin column method using the RNeasy Mini Kit (QIAGEN, Valencia, CA, U.S.A.), including on-column DNA digestion using the RNase-free DNase set (QIAGEN). Total RNA was reverse-transcribed into cDNA using a ReverTra Ace qPCR Kit (TOYOBO, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…12) The DAC analogue azacytidine was found to decrease the global level of DNA methylation and to downregulate DNMT1 and DNMT3a gene transcription in HCT116 cells at 3 to 4 d. 21) We also examined the DNA demethylating effects of DAC on various solute carrier (SLC) transporters in 4 human colon cancer cell lines, and found that DAC increased the mRNA levels of four SLC transporters examined in HCT116 cells. 22) Since DAC has various effects on DNA demethylation and cell survival in HCT116 cells, DAC may be taken up intracellularly to markedly high levels, and this DAC uptake may be related to the effects of DAC on DNA demethylation and cell survival in HCT116 cells. In the present study, we attempted to characterize the cellular uptake of uridine and DAC, and showed that DAC was mainly taken up by ENT1, similar to uridine, a typical substrate for ENT1, in HCT116 cells.…”
mentioning
confidence: 99%